Fourth Five Year Plan and Annual Plan 1969-70 Rajasthan - Planning Commission (Planning Commission, 1973)
By the time the Second Five Year Plan was drawn up, the conditions in the State had largely stabilized. the Second Plan was, therefore, formulated in a more realistic and scientific manner, ne emphasis on Agriculture, Irrigation and Power continued and a number of major Irrigation and rower schemes were launched during this period. An effort was made to direct the energies of the people who had now begun to appreciate the need and scope of the programmes of development into constructive channels. Village Panchayats were organized to associate the people with the processes of development. the Development Blocks also provided an effective forum for mobilizing the efforts of the people for productive purposes. In fact the old connotation given to state administration with its emphasis on regulation and control gave place to a new outlook which was steadily developing that of a well pre-state.
Planning Department, Government of Rajasthan